Ảnh hưởng của nano silica biến tính silan đến khả năng bảo vệ chống ăn mòn của màng sơn epoxy giàu kẽm - Dương, Nguyễn Thùy; Xuân Hằng, Tô Thị; Trúc, Trịnh Anh; Vũ, Phạm Gia; Trước, Bùi Văn; Hoàng, Thái (Vietnam Journal of Chemistry, 2016)
Zinc rich coatings are the best effective primers for corrosion protection of carbon steel in aggressive conditions. For traditional zinc rich primer the zinc content is very high, more than 90 wt.%. The coating adhesion is decreased with the increase of zinc content, so that it is necessary to decrease the zinc content by using additives. In this study the nano silica modified by N-(2-Aminoethyl)-3-aminopropyltrimethoxysilane was prepared and incoporated in zinc rich epoxy coatings containing 85 wt.% zinc powder. The corrosion protection performance of coatings was evaluated by electrochemical impedance spectroscopy. The results obtained show that the presence of nano silica improved corrosion protection of zinc rich epoxy coating and the best protection was obtained with 3 wt.% nano silica. Keywords. Silane modified nano silica, corrosion protection, electrochemical impedance spectroscopy, zinc rich coating.